Influence of solvent use on apical extrusion during removal of Resilon™ from root canals - Vukoje, Karolina; Veljović, Tanja; Mirnić, Jelena; Maletin, Aleksandra; Tadić, Ana (Vojnosanitetski pregled, 2023)
Background/Aim. During retreatment, filling material and debris may extrude and trigger an inflammatory reaction of periapical tissues. Resilon™ has not been investigated in terms of solvent use and influence on apical extrusion during retreatment. The aim of the study was to evaluate the amount of apically extruded debris during Resilon™ removal using ProTaper (PT), Twisted File (TF), and Hedstrom instruments, with and without solvent. Methods. In total, 72 extracted teeth with single canals were used. Canals were prepared with PT Universal (F2) and filled with Resilon™ and RealSeal sealer before being assigned randomly to 6 groups (n = 12 in each group). Retreatment in Groups 1–3 was done with PT, TF, or Hedstrom instruments, without solvent. In Groups 4–6, the same instruments were used with chloroform. Apically extruded debris was collected in a simulated periapical environment and assessed visually. Additionally, the time required for retreatment was recorded. Data were analyzed statistically using the Mann-Whitney U test, with a significance level of 0.05. Results. There were no significant differences in apical extrusion debris between groups (p > 0.05) regarding solvent use. Rotary instruments, without solvent, were associated with significantly less debris extrusion when compared with hand files (p < 0.05). When solvent was used, rotary instruments caused a higher degree of extruded material, which was similar to the results of hand instruments. Conclusion. The use of rotary instruments without solvent resulted in a lower degree extrusion of Resilon ™ material compared to hand instruments, while greater caution is advised in the presence of solvent when rotary instruments are used to remove this material.
Keywords: dental instruments; resilon sealer; root canal filling materials; solvents